Phylogeny, Multiple Antibiotic Resistance Index and BiofilmCharacterization of Mannheimia species Isolated from ClinicalCases of Pneumonia in Small Ruminants - Thatavarthi, Swaroop N S R K M; Sivarama , Krishna G; Supriya, A R; Anand , Kumar P (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
AbstractMannheimia is a Gram-negative, bipolar organism that is frequently involved in respiratory infections of bovines and small ruminants. In  the present study, a total of 92 nasal swab samples were examined from enzootic pneumonia cases of sheep and goat, out of which 30  Mannheimia isolates have been identified. The 16S rRNA sequence analysis of the isolate revealed a close genetic distance between the  Mannheimia species from different geographical regions. However, it formed a separate clade in the phylogenetic tree and the isolate  is closely related to the M. hemolytica and M. caviae species. Three methods (Standard Tube method, Congo Red method and Microtiter  Plate assay) were evaluated for identifying the biofilm forming Mannheimia isolates. Among them, Microtiter plate assay was the best  method for quantification of biofilm production, by which 29 out of 30 isolates were identified as biofilm producers. In antibiogram  study, the Mannheimia isolates exhibited resistance towards ampicillins, gentamicin, co-trimoxazole, tetracyclines and amoxicillin. All  30 isolates developed a multiple antibiotic resistance index (MAR) of more than 0.2. This indicates that there is a potential threat of  antimicrobial resistance (AMR) transmission through food animals. In conclusion our study provides insights into the genetic relation  between Mannheimia from India with other Mannheimia species from a different geographical region, and their capabilities of biofilm  production.
Keywords: Biofilms; Mannheimia; MAR-index; 16S rRNA; Phylogeny